Phycology - Lee, Robert Edward 1942- (New York, NY Cambridge University Press, 2018)
Phycology is the study of algae, the primary photosynthetic organisms in freshwater and marine food chains. Since the publication of the first edition in 1981, this textbook has established itself as a classic resource on this subject. Aimed at upper-level undergraduate and graduate students in phycology, limnology and biological oceanography, this revised edition maintains the format of previous editions, whilst incorporating the recent developments in the field such as: the potential and challenges of producing algae biofuel; the proliferation of algal toxins; and the development of new molecular tools and technologies on ancestry, phylogeny, and taxonomy of algae.--Provided by publisher.
Includes bibliographical references and index.
Keywords: Algology